Does Overtime Matter for Firm Performance: Evidence from Taiwan? - Ni, Yensen; Ho, Ting-Hsun; Liao, Yulu; Huang, Shih-Hui (Technium Social Sciences Journal, 2024)
By employing the unique data related to employee overtime complaints about the firms listed in the financial industry of Taiwan Stock Exchange, we explore whether firm performance would be affected by several overtime complaints issues including complaints of maximum working hours exceeded, overtime without pay, and overtime without records. We then reveal the following essential findings. First, the firms with employee overtime complaints would not enhance firm performance. Second, complaints of maximum working hours exceeded would have significant negative impacts on firm performance as compared with firm performance affected by either complaints of overtime without records or complaints of overtime without pay, indicating that employee’s complaints about overtime should not be neglected by enterprises. Third, we still show that the firm with better financial performance such as higher net profit ratio and well-functioned board structure like small board size would have better firm performance.